Intraseasonal variability of wintertime frontal activity and its relationship with precipitation anomalies in the vicinity of South America - Blazquez, Josefina (2015)
The intraseasonal variability of the frontal activity and its connection with the variability of the atmospheric circulation and precipitation in the Southern Hemisphere is studied. The frontal activity is defined as the relative vorticity times the local temperature gradient. A band-pass filter was applied to retain the intraseasonal timescales. An empirical orthogonal function analysis was applied to the filtered frontal activity anomalies. The two main modes show positive and negative centers located mainly over the southern Pacific Ocean and South American sector and are in quadrature with each other. A similar pattern was found when the main modes of intraseasonal variability of the 500 hPa geopotential height were projected on the frontal activity, suggesting that the variability of fronts are influenced by the variability of the large scale atmospheric circulation. Moreover, the precipitation anomalies projected on the main modes of both frontal activity and 500 hPa geopotential height show similar structures, especially over the southern Pacific Ocean and South America, which may indicate that the variability of fronts controls the variability of precipitation. The lagged regression of the time series of the frontal activity areally-averaged over one of the centers of action against the frontal activity anomaly field shows at lags −8 and 8 a similar pattern, suggesting a period of around 17 days for each mode. Moreover, lagged regression between times series of frontal activity and precipitation anomalies reveals an opposite pattern between southeastern South America and southern Chile, being precipitation anomalies over these two regions anti-correlated due to the frontal activity.